Unlocking the antioxidant and antibacterial potential of exopolysaccharides produced by endophytic fungi (Aspergillus fumigatus and Preussia isabellae) isolated from Tanzania’s mangroves - Bhoke Marwa Nyaisaba; Rose Justus Masalu; Hawa Myovela; Cyprian Beda Mpinda (BMC Biotechnology)
Abstract The investigation of the exopolysaccharide (EPS) produced by mangrove endophytic fungi is of significant importance. In the present work, EPS produced by endophytic fungi (Aspergillus fumigatus and Preussia isabellae) through submerged fermentation was analyzed. A. fumigatus produced significantly (p < 0.05) higher EPS (AF-EPS) (2.13 ± 0.38 g/L) than that produced by P. isabellae (PI-EPS) (1.04 ± 0.17 g/L). Fourier transform infrared spectra revealed varying degrees of functional groups associated with polysaccharides, thereby verifying the presence of EPS. In both EPS extracts, galactose and glucose were the major monomers detected. The antioxidant activities and anti-bacterial ability of the AF-EPS and PI-EPS were determined via 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2’-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) assays. Results revealed that AF-EPS and PI-EPS exhibited notable DPPH and ABTS radical scavenging capacities. AF-EPS, depicted higher antioxidant capacity, at a concentration of 5.0 mg/mL, could scavenge 70.92 ± 1.77% DPPH free radical and 53.74 ± 3.03% of ABTS free radical. Moreover, the antibacterial competence of each EPS was evaluated against four pathogenic bacteria using disk diffusion methodology. The bacterial inhibition effect of AF-EPS and PI-EPS on Gram-positive bacteria was greater than that of Gram-negative bacteria. Therefore, these findings suggest that AF-EPS and PI-EPS could be used as potential antioxidant and antibacterial agents for various applications, however, further exploration is necessary to investigate possible applications and the underlying mechanisms of these bioactive EPSs.